You will never walk alone : relationship strength and customer retention. - Koh, Shu Er. (2008)
Through this research study, it is observed that developing a close relationship with customers is essential. Maintaining good customer relationship play a part in establishing and retaining their loytalty, which results in positive Word-of-Mouth (WOM) and an increase in Degree of Tolerance.